NARRATIVE TRANSFORMATION IN BECAUSE OF WINN-DIXIE: A STRUCTURALIST APPROACH - Agung Wijianto; Fardan Rezkiawan Faida (Language Literacy: Journal of Linguistics, Literature, and Language Teaching)
This study aims to find the character Winn-Dixie’s narrative function in Kate DiCamillo’s Because of Winn-Dixie using A.J. Greimas’ actantial model. While previous research often focused on the novel’s emotional and psychological themes, this paper offers a structuralist approach to highlighting how narrative functions operate beneath the surface through the usage of actantial models and isotopes. The study uses descriptive qualitative method to examine narrative sequences to show how Winn-Dixie facilitates Opal’s movement from loneliness to connection, and from emotional fragmentation to relational wholeness. The findings demonstrate Winn-Dixie’s structural role as a helper actant and catalyst for the protagonist’s emotional transformation and that Winn-Dixie is not merely a symbolic or emotional figure but an essential structural force that shapes the novel’s progression and coherence. This research contributes an innovative perspective by applying classical structuralist theory to contemporary children’s literature, thereby enriching both narrative studies and literary criticism in the field.